THE PRACTICE OF INDEPENDENT LEARNING AND ITS IMPLICATIONS FOR STUDENTS’ LEARNING IN CLASSROOMS AND EDUCATIONAL INSTITUTIONS - Kartika, I Made; Anom Kumbara, A.A. Ngurah; Suda, I Ketut; Mudana, I Gede (E-Journal of Cultural Studies, 2022)
This article examines the practice of independent learning and its implications for students, the learning process in classrooms, and educational institutions.The policy of independent learning is the policy of the Minister of Education and Culture, which includes four main programs, namely the replacement of USBN into school exams, the replacement of the national exam with a minimum competency assessment and character survey, the implementation of a 1-sheet lesson plan, and the application of zoning-based new student admissions. The application of independent learning at the Denpasar City Public High School, especially at SMA Negeri 3 and SMA Negeri 8 was held starting from the 2019/2020 academic year. However, in practice there are still some obstacles faced by the school management. The writing of this article uses a qualitative descriptive method, with a cultural studies approach. This research found several things, among others: First, on the psychological aspect of implementing the independent learning policy, especially with regard to the replacement of USBN into a school exam and the National Examination as a minimum competency assessment, at least it can reduce the psychological burden of students in facing these exams. Second, in the didactic aspect, the application of this free learning policy can provide flexibility for teachers in terms of finding and finding various learning strategies and methods to develop PAIKEM learning. Third, in the sociological and juridical aspects, the implementation of this free learning policy can encourage the realization of a sense of justice for the Indonesian people, in terms of obtaining equal opportunities to enjoy quality education. Keywords: Freedom of Learning, National Examination, USBN, PPDB based on zoning